Heart Rate Variability Exhibits Complication-Dependent Changes Postsurgery. (November 2013) - Scheffler, Patrick; Muccio, Salvatore; Egiziano, Giordano; Doonan, Robert J.; Yu, Alice; Carli, Franco; Daskalopoulou, Stella S.
"Surgical stress response" is tissue damage postsurgery, leading to a systemic response (inflammation, sympathetic upregulation, and release of vasoactive chemicals), which is typically measured by C-reactive protein (CRP). We assessed arterial stiffness and heart rate variability (HRV)—additional parameters reflecting autonomic and vascular functions—in this response and their potential associations with postoperative complications. In 47 participants undergoing abdominal surgery, CRP, arterial stiffness, and HRV were measured pre- and postoperatively (days 1 and 2). C-reactive protein was significantly higher postoperatively in participants experiencing complications but not preoperatively. Compared to participants without complications, those with complications had increased HRV and pnn50 (time domain) and tendency toward increasing low-frequency/high-frequency ratio (frequency domain) on postoperative day 2. Therefore, time and frequency domain HRV parameters show perioperative changes in relation to complication development. These findings suggest the applicability of this noninvasive technology to a variety of abdominal operations. Larger studies need to confirm these findings.